A toxicity risk index, an index for warning idiosyncratic drug toxicity. Issue 9 (10th May 2013) - Morimoto, Miyoshi; Samizo, Kazuo; Ohta, Shin; Mizuma, Takashi; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract Drug toxicity impedes drug development and its clinical use. In the present study, a toxicity risk index (TRI), which is an index for warning idiosyncratic drug toxicity (IDT), was proposed. The TRI of drugs was defined as a function of dose, pharmacokinetic parameters, and toxicokinetic data from covalent binding experiment. Twenty drugs, which were classified into three categories by a report (Nakayama S, Atsumi R, Takakusa H, Kobayashi Y, Kurihara A, Nagai Y, Nakai D, Okazaki O. 2009. Drug Metab Dispos 37:1970–1977), were studied with TRI. The three categories were BBW (drugs with a block box warning for IDT), WNG (drugs without a black box warning but with a warning for IDT), and SAFE (drugs without any warning). The TRIs of drugs classified as SAFE were distinctly different from those classified as BBW. The TRI of the SAFE drugs were lower than 0.456 (nmol/mg protein). In contrast, the TRI of the BBW drugs were higher than 1.10 (nmol/mg protein). These results warned us that a drug candidate, where the TRI is higher than 1.0 nmol/mg protein, should be categorized as a BBW drug. Further study with more data of TRI will give a cutoff value with a statistical meaning. Thus, TRI may be useful for decision making in drug development and its clinical use. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3447–3450, 2013